Defining surgical criteria for empty nose syndrome: Validation of the office‐based cotton test and clinical interpretability of the validated Empty Nose Syndrome 6‐Item Questionnaire. (27th March 2017) - Thamboo, Andrew; Velasquez, Nathalia; Habib, Al‐Rahim R.; Zarabanda, David; Paknezhad, Hassan; Nayak, Jayakar V.
Abstract : Objectives/Hypothesis: The validated Empty Nose Syndrome 6‐Item Questionnaire (ENS6Q) identifies empty nose syndrome (ENS) patients. The unvalidated cotton test assesses improvement in ENS‐related symptoms. By first validating the cotton test using the ENS6Q, we define the minimal clinically important difference (MCID) score for the ENS6Q. Study Design: Individual case–control study. Methods: Fifteen patients diagnosed with ENS and 18 controls with non‐ENS sinonasal conditions underwent office cotton placement. Both groups completed ENS6Q testing in three conditions—precotton, cotton in situ, and postcotton—to measure the reproducibility of ENS6Q scoring. Participants also completed a five‐item transition scale ranging from "much better" to "much worse" to rate subjective changes in nasal breathing with and without cotton placement. Mean changes for each transition point, and the ENS6Q MCID, were then calculated. Results: In the precotton condition, significant differences ( P < .001) in all ENS6Q questions between ENS and controls were noted. With cotton in situ, nearly all prior ENS6Q differences normalized between ENS and control patients. For ENS patients, the changes in the mean differences between the precotton and cotton in situ conditions compared to postcotton versus cotton in situ conditions were insignificant among individuals. Including all 33 participants, the mean change in the ENS6Q between the parameters "a little better" and "about the same" was 4.25 (standard deviation [SD] = 5.79) and −2.00 (SD = 3.70), giving an MCID of 6.25. Conclusions: Cotton testing is a validated office test to assess for ENS patients. Cotton testing also helped to determine the MCID of the ENS6Q, which is a 7‐point change from the baseline ENS6Q score. Level of Evidence: 3b. Laryngoscope, 127:1746–1752, 2017